Becoming a preferred customer for supplier innovation resources - Huttunen, Oula (My University, 2021)
Supplier networks and relationships are a great source of competitive advantage for companies. Being able to leverage innovations from the supplier base can be a huge boost to the innovation efforts of a company. Developing a close relationship with a supplier can improve a company’s acquisition of resources and innovation ideas if the suppliers are more willing to dedicate their resources to benefit the customer than their competitors. However, companies are faced with scarcity of capable suppliers and the suppliers’ limited resources, which leads competent and desirable suppliers to allocate their resources and capabilities differently among their customers. Customer companies must therefore seek to become a preferred customer of the desired and capable suppliers. This thesis aims to offer ways to become a preferred customer of a supplier, with a focus on supplier innovation resourced. The research question of this thesis is “How can the commissioning company gain preferential customer treatment in terms of accessing supplier innovations?”. This commissioned thesis is conducted as a qualitative multiple-case study with semi-structured interviews. Utilizing the social exchange theory as a background, the theoretical section is based on preferred customer status and innovation management literature. The drivers for becoming a preferred customer and enablers of innovation sharing by the supplier are comprehensively researched. The empirical data is collected by interviewing selected suppliers of the commissioning company, their sourcing category managers and research & development representative of the commissioning company. These interview findings are then compared with the findings from the theoretical background to form conclusions and give recommendations to the commissioning company. This study concluded that a company that can develop a cooperative supplier relationship based on trust and offer high benefits with low costs to the supplier and does this better than the other customers of the supplier, is likely to become the preferred customer. This will enhance their access to the supplier’s innovation resources. There are multiple individual drivers that contribute to the process. These drivers influence the development of the preferred customer status through customer attractiveness or supplier satisfaction.

Toimittajaverkostot ja -suhteet ovat tärkeä kilpailukyvyn lähde yrityksille. Kyky hankkia innovaatioita ja ideoita toimittajaverkostosta voi olla merkittävä lisä yrityksen innovaatiokyvykkyyksissä. Läheisten toimittajasuhteiden kehittäminen parantaa yrityksen kykyä saada käyttöönsä toimittajien innovaatioresursseja, jos toimittajat ovat halukkaampia jakamaan kyvykkyyksiään mieluummin kohdeyritykselle kuin kohdeyrityksen kilpailijoille. Yritykset joutuvat kuitenkin kohtaamaan kyvykkäiden toimittajien niukkuuden ja toimittajien resurs-sien rajallisuuden, joka johtaa toimittajat allokoimaan resursseja ja kyvykkyyksiä eri tavoin asiakkaidensa kesken. Asiakasyritysten tulee siksi pyrkiä pääsemään ensisijaiseksi asiakkaaksi kyvykkäiden toimittajien silmissä. Tämä tutkielma pyrkii tarjoamaan keinoja ensisi-jaiseksi asiakkaaksi pääsemiseksi keskittyen erityisesti toimittajan innovaatioresurssien näkökulmaan. Tutkielman tutkimuskysymys on “Miten toimeksiantajayritys pystyy saamaan ensisijaisen asiakkaan aseman toimittajan innovaatioresurssien saamiseksi?” Tämä tutkielma on tehty toimeksiantona. Tutkielma on toteutettu monitapaustutkimuksena, jossa on puolistrukturoituja haastatteluita. Käyttäen sosiaalisen vaihdon teoriaa taustana, teoriaosuus käsittelee ensisijaisen asiakkuuden saavuttamisen ja innovaatioiden hallinnan kirjallisuutta. Yksittäiset ajurit ensisijaiseksi asiakkaaksi pääsemiseksi ja toimittajainnovaatioiden jakamisen edellytykseksi on tutkittu kattavasti. Empiirinen data on kerätty haastattelemalla toimeksiantajan toimittajia, hankinnan edustajia ja kehitysedustajaa. Haastattelutuloksia on verrattu löydöksiin tutkimuskirjallisuudesta johtopäätösten ja suositusten tekemiseksi toimeksiantajalle. Tutkielman johtopäätös on, että yritys, joka pystyy kehittämään yhteistyöhön ja luottamukseen perustuvan toimittajasuhteen, joka tarjoaa suurta hyötyä toimittajalle matalilla kustannuksilla, ja tekee sen paremmin kuin toimittajan muut asiakkaan, nousee todennäköisesti ensisijaiseksi asiakkaaksi toimittajan silmissä. Tämä parantaa asiakasyrityksen mahdollisuuksia hyödyntää toimittajan innovaatioresursseja. Ensisijaisen asiakkuuden kehittymiseen vaikuttaa moni yksittäinen tekijä, jotka voidaan jaotella asiakkaan houkuttelevuuteen tai toimittajan tyytyväisyyteen vaikuttaviin tekijöihin.
Keywords: Preferred customer, innovations, supplier management, social exchange theory